Nepal-India Relations: India’s Covertly and Overtly Imposed Blockades - Timalsina, Saroj Kumar; Karki, Jantaraj (Swarnadwar, 2025)
The following paper aims to clarify India’s actual involvement in Nepal during three blockades. In order to achieve the study’s objectives, the researcher employed secondary sources of data and analyzed it using both analytical and descriptive methods of information interpretation. Scholarly books, articles, opinions, social media-based information (Facebook, Twitter, Instagram, TV interviews, News, Views); viewpoints available on paper and electronic media have been employed under the category of secondary source of information. In 1969, after Nepal constructed the Araniko Highway connecting Kathmandu with China and established Tatopani as a trading route with the northern neighbor, India became displeased and blocked the flow of commodities into Nepal. Even though the 1969 economic embargo only lasted a short while, it caused problems for Nepal’s seamless supply of some goods, like salt and spice products, because the country was dependent on India for these items. India was enraged by Nepal’s attempts to decrease its dependence on India alone. India imposed a second embargo in 1988–1989 that lasted for 15 months. The dissatisfaction of Nepal and India over the renewal of trade and transit treaties was the excuse for it, and the political reason might be the contrast between parliamentary and royal government. The third blockade, which was informally enforced by India under the guise of a constitution that was exclusive to the Madhesi people, lasted for almost five months. The author of the article examined the rationale for and the impacts of India’s blockades of Nepal.